Digital M&A, digital innovation, and firm performance: an empirical investigation. Issue 1 (2nd January 2021) - Hanelt, André; Firk, Sebastian; Hildebrandt, Björn; Kolbe, Lutz M.
ABSTRACT: Aiming to support digital innovation endeavours, industrial-age companies increasingly acquire firms that heavily build upon digital technologies. Related research has raised serious concerns regarding the prospects of such plans, yet has not focused the particular context of digital mergers and acquisitions (M&A). Drawing on a knowledge-based perspective as well as the particularities of digital technologies and the context of digital innovation, we theorise the link between digital M&A, a digital knowledge base on the part of the acquirer, and the consequences for digital innovation and firm performance. We employ panel data regressions to a longitudinal dataset of the world's largest automobile manufacturers. Our findings suggest that executing digital M&A contributes to building the digital knowledge base of industrial-age firms, which in turn enables them to drive digital innovation. Our findings further indicate that digital innovation improves firm performance of industrial-age firms. We discuss implications for information systems research about M&A and digital innovation as well as recommendations for managerial practice.